Composite carbon-based wave-absorbing material and preparation method thereof
By adding MnFe2O4 composite and biomass carbon powder to the carbon-based absorbing material, holes are formed on the modified PVC surface, which solves the problem of low magnetic permeability of existing carbon-based absorbing materials and significantly improves the absorbing performance.
Patent Information
- Application Number
- CN202510114562.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing methods for preparing carbon-based absorbent materials, the magnetic permeability is low and there are certain limitations.
By mixing soluble manganese salt, soluble iron salt and PVC powder with biomass carbon powder, hydrothermal reaction is carried out to generate MnFe2O4 complex. In the modified PVC surface, a large number of holes are formed on the modified PVC surface to improve the wave absorption performance.
The comprehensive absorption performance of PVC materials is significantly improved. By controlling the content of manganese ferrite and carbon powder, the absorption performance of the sample is regulated. The content of manganese ferrite and biomass carbon powder has a significant nonlinear influence on the absorption performance of the sample.
Smart Images

Figure CN119899479A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to a composite carbon-based absorbing material and a preparation method thereof. Background Art
[0002] As a special material, absorbing materials can absorb or greatly weaken electromagnetic wave energy, and play a vital role in modern science and technology. Its principle is mainly based on the transmission characteristics of electromagnetic waves and electromagnetic loss mechanisms inside the material. When electromagnetic waves encounter absorbing materials, they interact with the charges and magnetic moments inside the material, and then convert them into heat energy or consume other forms of energy, thereby achieving the purpose of absorbing and attenuating electromagnetic waves.
[0003] The application field of absorbing materials has been gradually expanded with the continuous advancement of technology, and the process has become more mature. The types and performance of absorbing materials have been continuously optimized and improved, from the initial alloy absorbing materials, to carbon fiber absorbing materials, to magnetic absorbing materials and porous materials. Today, absorbing materials have become an independent discipline system with specialized research institutions and manufacturers, and are widely used in military, electronics, communications, aerospace and other fields. They are widely used in the field of absorbing materials worldwide. Absorbing materials have developed rapidly in recent years, such as: carbon fiber materials, carbon nanotube materials, ferrite materials, conductive polymer materials, etc. Among them, carbon-based absorbing materials have the characteristics of lightness, durability, high temperature resistance, and corrosion resistance. However, the magnetic permeability of carbon-based absorbing materials prepared by existing preparation methods such as chemical vapor deposition, electrospinning and template methods is low, and there are certain limitations. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a composite carbon-based absorbing material and a preparation method thereof. The present invention utilizes manganese ferrite and bio-carbon powder to modify polyvinyl chloride powder so that the modified polyvinyl chloride has better absorbing performance.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a composite carbon-based absorbing material comprises the following steps: Soluble manganese salt, soluble iron salt and PVC powder are mixed and dissolved with biomass carbon powder in water, and then sodium acetate is added to obtain a mixed solution. An alkaline solution is added to the mixed solution to adjust the pH value, and a hydrothermal reaction occurs. The PVC powder is used as a reaction matrix and undergoes a hydrothermal carbonization reaction with the biomass carbon powder to destroy the C-Cl bond in the PVC, and the C-Cl bond is converted into a CO bond, a C=O bond and a C=C bond. The soluble manganese salt and the soluble iron salt react under hydrothermal conditions to generate MnFe2O4 composite dechlorinated PVC powder.
[0006] After that, post-processing is performed to obtain a composite carbon-based absorbing material.
[0007] The present invention uses PVC powder as the main reaction matrix, adds carbon powder to carry out hydrothermal carbonization reaction, destroys C-Cl bonds in PVC, and converts C-Cl bonds into CO bonds, C=O bonds and C=C bonds. Soluble manganese salt and soluble iron salt are used to generate MnFe2O4, and the generated MnFe2O4 can be compounded with dechlorinated PVC. CH3COONa helps the above substances to fully dissolve. Biochar can effectively modify waste PVC, so that the surface of the modified PVC has a large number of holes, which provides a large number of sites for the compounding of manganese ferrite; the sample's wave absorption performance can be adjusted, and the comprehensive wave absorption performance of the PVC material can be significantly improved by controlling the manganese ferrite content and the carbon powder content.
[0008] In a preferred embodiment of the present invention, the molar ratio of the soluble manganese salt to the soluble iron salt is 1-2.5:2-5.
[0009] In a preferred embodiment of the present invention, the mass ratio of the soluble manganese salt to the PVC powder is 2-5:4.
[0010] In a preferred embodiment of the present invention, the mass ratio of PVC powder to carbon powder is 4:1-2.
[0011] In a preferred embodiment of the present invention, the usage ratio of soluble manganese salt to water is 0.2 g~0.5 g:50 mL.
[0012] In a preferred embodiment of the present invention, the hydrothermal reaction temperature is 180° C. to 200° C., and the hydrothermal reaction time is 600 min to 700 min.
[0013] In a preferred embodiment of the present invention, the soluble manganese salt is MnCl24H2O, and the soluble iron salt is Fe(NO3)3·9H2O.
[0014] In a preferred embodiment of the present invention, the pH is adjusted to ≥10.
[0015] In a preferred embodiment of the present invention, the post-processing operation is: the sample is filtered and separated, and the filter cake is washed with water to remove impurity ions such as Cl-, and then the filter cake is dried, and the dried filter cake is ground with paraffin wax and pressure is maintained to obtain a compressed sample.
[0016] Another object of the present invention is to provide a composite carbon-based absorbing material prepared by any of the preparation methods described above.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses PVC powder as the main reaction matrix, adds carbon powder to carry out hydrothermal carbonization reaction, destroys C-Cl bonds in PVC, and converts C-Cl bonds into CO bonds, C=O bonds and C=C bonds. Soluble manganese salts and soluble iron salts are used to generate MnFe2O4. The generated MnFe2O4 can be compounded with dechlorinated PVC. CH3COONa helps the above substances to fully dissolve. Biochar can effectively modify waste PVC, so that there are a large number of holes on the surface of the modified PVC, which provides a large number of sites for the compounding of manganese ferrite. The sample's wave absorption performance can be adjusted. By controlling the manganese ferrite content and the carbon powder content, the comprehensive wave absorption performance of the PVC material can be significantly improved.
[0018] 2. Biochar can effectively modify waste PVC, so that there are a large number of holes on the surface of the modified PVC, which provides a large number of sites for the recombination of manganese ferrite; the sample's absorbing performance is adjustable. The present invention can control the sample's absorbing performance by controlling the manganese ferrite content and the carbon powder content. The content of manganese ferrite and biomass carbon powder has a significant nonlinear effect on the sample's absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The APM-2 sample of the present invention has a post-reaction solution (a) and a pressed tablet shape (b). Figure 2 The XRD patterns of PM, APM-1, APM-2 and APM-3 of the present invention are shown in FIG.
[0020] Figure 3 These are SEM images of the samples of the present invention, (a) and (b) are APM-1, (c) and (d) are APM-2.
[0021] Figure 4 The dielectric constants of samples PM, APM-1, APM-2 and APM-3 of the present invention, (a) the real part of the dielectric constant, (b) the imaginary part of the dielectric constant.
[0022] Figure 5 Magnetic permeabilities of samples PM, APM-1, APM-2 and APM-3 of the present invention, (a) real part of magnetic permeability, (b) imaginary part of magnetic permeability.
[0023] Figure 6 The dielectric loss diagram (a) and magnetic loss diagram (b) of samples PM, APM-1, APM-2 and APM-3 of the present invention.
[0024] Figure 7 This is the magnetic tape loop of the sample APM-2 of the present invention.
[0025] Figure 8 These are the reflection loss diagrams of the samples of the present invention: (a) PM, (b) APM-1, (c) APM-2, and (d) APM-3.
[0026] Fig. 9 These are the reflection loss diagrams of the samples of the present invention: (a) APM-2, (b) APM-5, (c) APM-6, and (d) APM-7. DETAILED DESCRIPTION
[0027] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0029] Example 1 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.1 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0030] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0031] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0032] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0033] (5) The dried filter cake was ground to obtain the original sample. Then 0.03 g of the original sample and 0.07 g of paraffin were ground and the pressure was maintained at 8 MPa for 30 s to obtain a pressed tablet sample, which was recorded as APM-2. The solution and pressed tablet shape of the APM-2 sample after reaction were as shown in Figure 1 shown.
[0034] Example 2 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.1979 g MnCl24H2O, 0.808 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.1 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0035] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0036] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0037] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0038] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was pressurized at 8 MPa for 30 s to obtain a compressed sample, which was recorded as APM-1.
[0039] Example 3 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.3958 g MnCl24H2O, 1.616 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.1 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0040] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0041] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0042] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0043] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was pressurized at 8 MPa for 30 s to obtain a compressed sample, which was designated as APM-3.
[0044] Example 4 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.4948 g MnCl24H2O, 2.020 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.1 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0045] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0046] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0047] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0048] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was kept under pressure at 8 MPa for 30 s to obtain a compressed sample, which was designated as APM-4.
[0049] Example 5 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.2 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0050] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0051] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0052] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0053] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was pressurized at 8 MPa for 30 s to obtain a compressed sample, which was designated as APM-5.
[0054] Comparative Example 1 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O and 0.4 g PVC powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0055] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0056] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0057] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0058] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was kept under pressure at 8 MPa for 30 s to obtain a compressed sample, which was recorded as PM.
[0059] Comparative Example 2 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O and 0.4 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0060] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0061] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0062] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0063] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was kept under pressure at 8 MPa for 30 s to obtain a compressed sample, which was recorded as AM.
[0064] Comparative Example 3 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.3 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0065] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0066] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0067] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0068] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was pressurized at 8 MPa for 30 s to obtain a compressed sample, which was designated as APM-6.
[0069] Comparative Example 4 A method for preparing a composite carbon-based absorbing material comprises the following steps: (1) First, place 0.2969 g MnCl24H2O, 1.212 g Fe(NO3)3·9H2O, 0.4 g PVC powder and 0.4 g carbon powder in a beaker, add 50 mL deionized water, stir at 50°C for 30 min, then add 1.0 g CH3COONa and continue stirring for 60 min.
[0070] (2) After stirring, add an appropriate amount of KOH solution to make the solution pH ≥ 10, and then continue stirring at 50 °C for 120 min.
[0071] (3) The fully stirred mixed solution was charged into a reactor and maintained at 200 °C for 660 min.
[0072] (4) After the sample solution has cooled, use a vacuum filter to separate the sample and wash the filter cake several times with deionized water to remove the Cl - etc. impurity ions, and then the filter cake is dried.
[0073] (5) The dried filter cake was ground to obtain the original sample. Then, 0.03 g of the original sample and 0.07 g of paraffin were ground and the mixture was pressurized at 8 MPa for 30 s to obtain a compressed sample, which was named APM-7.
[0074] The experimental reagents and instruments are shown in Tables 1 and 2.
[0075] Table 1 Experimental reagents Table 2 Experimental instruments Experimental principle of the present invention: In this experiment, PVC powder is used as the main matrix of the reaction, and the main function of biomass carbon powder is to carry out hydrothermal carbonization reaction, destroy the C-Cl bond in PVC, and convert the C-Cl bond into CO bond, C=O bond and C=C bond. MnCl2·4H2O and Fe(NO3)3·9H2O are used to generate MnFe2O4, and the generated MnFe2O4 can be compounded with the dechlorinated PVC, CH3COONa can help the above substances to fully dissolve, and KOH provides an alkaline environment for the generation of MnFe2O4.
[0076] The invention controls the amount of MnFe2O4 generated by controlling the ratio of MnCl2·4H2O to Fe(NO3)3·9H2O, and the ratio of MnCl2·4H2O to Fe(NO3)3·9H2O is 1 mmol:2 mmol, 1.5 mmol:3 mmol, 2 mmol:4mmol, and 2.5 mmol:5 mmol, respectively. The influence of the carbon powder content on the absorbing performance of the sample is also studied, and the samples finally obtained include PVC-based manganese ferrite absorbing material without carbon powder, denoted as PM, carbon-based manganese ferrite absorbing material without PVC, denoted as AM, and PVC-based manganese ferrite and carbon powder absorbing material, denoted as APM.
[0077] Performance Testing Phase Characterization Data and Analysis PVC material itself is usually non-magnetic or weakly magnetic, and its magnetic permeability is close to 1. In order to improve its magnetic permeability, MnFe2O4 is used to compound PVC. In order to observe the synthesis of MnFe2O4, the crystal structure of the sample is analyzed by X-ray diffractometer. The results are as follows: Figure 2 As shown. In the sample spectra measured, characteristic diffraction peaks appeared at 2θ of 18.1°, 29.7°, 34.9°, 36.6°, 42.5°, 56.2° and 61.7°, which correspond to the (111), (220), (311), (222), (400), (511) and (440) crystal planes of the manganese ferrite standard card (PDF#10-0319), respectively. The peak shape is complete, and the crystallization effect of MnFe2O4 is good. Moreover, the addition of biomass carbon powder makes the diffraction peak of MnFe2O4 stronger, indicating that carbon powder is conducive to the grain growth of MnFe2O4.
[0078] Morphological characterization data and analysis The APM-1 and APM-2 samples were characterized by SEM. The characterization results are shown in Figure 3 As shown in Figures (a) and (b), there are many holes on the surface of the APM-1 sample. The hole distribution is uneven, and the maximum hole diameter is about 60nm. In addition, there are a small amount of granular substances on its surface, which shows that the carbon powder reacts well with PVC. The carbon powder successfully destroys the C-Cl bond of PVC and changes the structure of PVC. This substance is the product of the hydrothermal carbonization reaction of PVC. As can be seen from Figures (c) and (d), a large amount of granular substances are attached to the surface of the APM-2 sample. These particles are distributed in clusters on the sample surface. The particle diameter is about 10 nm. After clustering, the diameter is about 60 nm~100 nm. These particles are MnFe2O4 generated by the reaction of MnCl2 and Fe(NO3)3, and the MnFe2O4 generated by APM-2 is significantly more than that of APM-1.
[0079] Complex permittivity and complex magnetic permeability analysis In the microwave field, the real part of the dielectric constant represents its ability to store electric fields. The larger the real part, the stronger its ability to store electric fields. The imaginary part of the dielectric constant represents the material's ability to dissipate electric fields. The larger the imaginary part, the greater the dissipation and the more heat energy converted. Figure 4The dielectric constants of samples PM, APM-1, APM-2 and APM-3 are given. In general, the addition of carbon powder will increase both the real and imaginary parts of the dielectric constant of the sample, especially the real part of the dielectric constant, which increases more significantly, indicating that the carbon powder enhances the sample's ability to absorb electric fields more significantly, which may be related to the good conductivity of the carbon powder itself and the modification of PVC by the carbon powder. From (a), it can be seen that the real part of the dielectric constant of APM-1 is the largest, followed by APM-3, and the real part of the dielectric constant of APM-2 is smaller, and the difference between the latter two is not very large, indicating that the increase in the content of MnFe2O4 has a certain negative effect on the storage electric field ability of the modified PVC, but this effect has a certain valley value. From (b), it can be seen that the imaginary part of the dielectric constant of the material varies greatly in different frequency bands. Among them, the imaginary part of the dielectric constant of APM-2 is larger in the low and high frequency bands; the imaginary part of the dielectric constant of APM-3 is larger in the mid-frequency band; and the imaginary part of the dielectric constant of APM-1 does not have outstanding performance. This indicates that the increase in the content of MnFe2O4 has a certain positive effect on the ability of modified PVC to convert electrical energy into thermal energy, which may be related to the fact that MnFe2O4 materials are more susceptible to dielectric polarization.
[0080] Figure 5 The magnetic permeabilities of samples PM, APM-1, APM-2 and APM-3 are given. In general, the carbon powder does not improve the magnetic permeability of the samples much, and even has a certain negative effect on the real part of the magnetic permeability in the low and medium frequency bands. This phenomenon may be related to the low magnetic permeability of the carbon powder. However, at 12 GHz~13 GHz, the real and imaginary parts of the magnetic permeability of PM suddenly change. The real part rises to the peak and then drops to the bottom, while the imaginary part reaches the peak. This may be due to the difficulty of crystallization of MnFe2O4 on the surface of PVC without carbon powder and the uneven structure. In Figures (a) and (b), the real and imaginary parts of the magnetic permeabilities of APM-1, APM-2 and APM-3 are small in the low frequency band, but in the medium and high frequency bands, the real and imaginary parts of the magnetic permeability of APM-2 gradually increase, indicating that APM-2 has the strongest ability to absorb and dissipate magnetic fields.
[0081] Dielectric loss and magnetic loss analysis When comprehensively comparing the materials' ability to absorb radio waves or magnetic fields, their dielectric loss data or magnetic loss data will be analyzed. The larger the value, the stronger their ability to absorb radio waves or magnetic fields. Figure 6The dielectric loss and magnetic loss of samples PM, APM-1, APM-2 and APM-3 are given in Figure 1. By analyzing Figure (a), the following points can be drawn: (1) The dielectric loss value of the sample increases significantly after adding carbon powder, indicating that carbon powder will increase the sample's ability to absorb radio waves; (2) The effect of the content of MnFe2O4 on the sample's ability to absorb radio waves does not change linearly. As can be seen in Figure (a), APM-2 has the strongest ability to absorb radio waves. Too high or too low a content of MnFe2O4 is not the optimal solution to improve the sample's ability to absorb radio waves; (3) The dielectric loss at high frequencies is significantly higher than that at low and medium frequencies, indicating that the sample has a better ability to absorb radio waves at high frequencies. By analyzing Figure (b), the following points can be drawn: (1) At low and high frequencies, the addition of carbon powder has no significant effect on the sample's ability to absorb magnetic fields; (2) At medium and medium-high frequencies, the PM sample without carbon powder has a stronger ability to absorb magnetic fields, and at this time, carbon powder has a negative impact on the sample's ability to absorb magnetic fields; (3) In different frequency bands, the effect of MnFe2O4 content on the sample's ability to absorb magnetic fields is different and fluctuates greatly. In comparison, the APM-2 sample's ability to absorb magnetic fields is more stable.
[0082] In order to further analyze the magnetic properties of sample APM-2, the hysteresis loop of sample APM-2 was drawn, as shown in Figure 7 Obviously, the hysteresis loop of sample APM-2 presents a very narrow S shape, which is a soft magnetic material with high magnetic permeability, small coercive force and remanence, and is suitable for use as a wave absorbing material.
[0083] Reflection loss analysis Reflection loss is a comprehensive evaluation of the material's ability to absorb waves. The larger the absolute value of the minimum reflection loss, the wider the corresponding absorption frequency range and the better the material's ability to absorb waves. See the reflection loss of samples PM, APM-1, APM-2 and APM-3 for details. Figure 8 , the relevant values are shown in Table 3.
[0084] It can be seen from the relevant data that the effective absorption width of PM is very narrow, only 1.03 GHz, and it is difficult to use it in practice; the absolute value of the minimum reflection loss of APM-1 is large, reaching 40.13 dB, but the width is relatively narrow, which is suitable for selective absorption of high frequencies; the effective absorption width of APM-3 is large, reaching 2.76 GHz, but its minimum reflection loss is small, which is suitable for wide absorption of medium frequencies. The absolute value of the minimum reflection loss of sample APM-2 is 30.14 dB, and the absorption width is 2.31 GHz. The overall performance is very good, and it is suitable for high-frequency absorption.
[0085] Table 3 Relevant values of reflection loss of samples PM, APM-1, APM-2 and APM-3 In order to further analyze the effect of carbon powder content on the wave absorption performance of modified waste PVC, the reflection loss of samples APM-2, APM-5, APM-6 and APM-7 were compared. Fig. 9 , the relevant data are shown in Table 4. As the carbon powder content gradually increases, the wave absorption performance of the sample shows a downward trend. When the carbon powder content is high, such as samples APM-6 and APM-7, their absorption width becomes very narrow, only 0.68 GHz and 0.71 GHz respectively, which is almost of little practical value. This phenomenon may be due to the fact that there is too much carbon powder, and there is still some left after the complete hydrolysis reaction with PVC, thus affecting the wave absorption performance of the sample.
[0086] Table 4 Relevant values of reflection loss of samples PM, APM-1, APM-2 and APM-3 The present invention studies the modification of PVC materials by adding MnFe2O4 and biomass carbon powder, observes the wave absorbing properties of the modified samples, analyzes the data of the samples such as phase, surface morphology, dielectric constant, magnetic permeability, dielectric loss, magnetic loss and reflection loss, and finally draws the following conclusions: (1) Biomass carbon powder can successfully destroy the C-Cl bonds in PVC through hydrothermal carbonization reaction, change the PVC structure, and produce holes on its surface, making it easier to compound MnFe2O4.
[0087] (2) Through this experimental method, the characteristic diffraction peak of MnFe2O4 is obvious, the synthesis effect is good, the crystallinity is high, and the crystallization effect is good.
[0088] (3) The microwave absorption performance of the sample can be adjusted by controlling the content of manganese ferrite and the content of biomass carbon powder.
[0089] (4) The content of MnFe2O4 and biomass carbon powder has a significant nonlinear effect on the microwave absorption properties of the sample. Based on the data in this article, when the mass ratio of MnFe2O4, carbon powder and PVC is 0.886:0.25:1, the microwave absorption performance is the best, the minimum absolute value of reflection loss is 30.14 dB, and the absorption width is 2.31 GHz.
[0090] In summary, by adding appropriate amounts of MnFe2O4 and biomass carbon powder, the comprehensive microwave absorption performance of PVC materials can be significantly improved, which provides new possibilities for the application of PVC in the microwave field and can also alleviate the environmental pressure brought by waste PVC.
[0091] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.
[0092] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention belong to the protection scope of the present invention, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a composite carbon-based absorbing material, characterized in that: The following steps are involved: A soluble manganese salt, a soluble iron salt and PVC powder are mixed and dissolved in water with biomass carbon powder, and then sodium acetate is added to obtain a mixed solution, an alkaline solution is added to the mixed solution to adjust the pH, a hydrothermal reaction occurs, and the PVC powder is used as a reaction matrix to undergo a hydrothermal carbonization reaction with the biomass carbon powder to destroy the C-Cl bond in the PVC, and the C-Cl bond is converted into a CO bond, a C=O bond and a C=C bond, and the soluble manganese salt and the soluble iron salt react under hydrothermal conditions to generate MnFe2O4 composite dechlorinated PVC powder; After that, post-processing is performed to obtain a composite carbon-based absorbing material.
2. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: The molar ratio of soluble manganese salt to soluble iron salt is 1-2.5:2-5.
3. The method for preparing the composite carbon-based absorbing material according to claim 1, characterized in that: The mass ratio of soluble manganese salt to PVC powder is 2~5:
4.
4. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: The mass ratio of PVC powder to biomass carbon powder is 4:1~2.
5. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: The dosage ratio of soluble manganese salt to water is 0.2 g~0.5 g:50 mL.
6. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: The hydrothermal carbonization reaction temperature is 180℃~200℃, and the hydrothermal reaction time is 600 min~700 min.
7. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: The soluble manganese salt is MnCl2 4H2O, and the soluble iron salt is Fe(NO3)3·9H2O.
8. The method for preparing a composite carbon-based absorbing material according to claim 1, characterized in that: Adjust pH ≥ 10.
9. A composite carbon-based absorbing material obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Cited By
Preparation method and application of modified PVC adsorbent for gold extraction of carbonaceous gold ore
CN121378542A